QUALITY IMPROVEMENT OF COMPETENCY TEST OF AUTOMOTIVE SKILL IN SMK BY USING â10 MONTHS ONLINEâ MODEL - -, Abdurahman; -, Soesanto; -, Samsudi; -, Slameto (The Journal of Educational Development, 2014)
This study aims to find the management model of competency test implementation so industrial market will acknowledge the test certificates obtained by vocational high school (SMK) graduates. The study employs a Research and Development (R & D) without implementing the whole steps of R&D. The research begins with the preliminary step and then continues with FGD I in order to fix model I, then the model I become model II, and then model II ended by FGD II to be the model II which is validated by the experts and practitioners upon its feasibility. These procedures are conducted considering the research finding related to a policy change is hard to be implemented. The results of the study show that one validator assesses the model as âquite feasible to be implementedâ. Four validators conclude that the model is âfeasible to be implementedâ. Five validators categorize the model as âvery feasible to be implementedâ. The measurement of the model validity is 84.6%. Therefore, the competency test model " 10 months onlineâ is very feasible to be implemented. This outcome is well-embraced by the FGD participants. Based on interviews researchers with industry the findings of this researchÂ  wasÂ  good and the model is easy to implement. Likewise, internal assessors opinion this model is a new innovation and feasible. This study concludes that the competency test model of "10 months online " infeasible and provides a great opportunity for the industry to be involved in assessing the competency test because it is administered on Saturday and Sunday within 10 months. The involvement of industry world is expected to have a positive impact, i.e. the graduates are easier to get a job.